Novel Adipokines and Bone Metabolism. (8th January 2013) - Liu, Yuan; Song, Cheng-Yuan; Wu, Shan-Shan; Liang, Qiu-Hua; Yuan, Ling-Qing; Liao, Er-Yuan
Abstract : Osteoporosis is a serious social issue nowadays. Both the high morbidity and its common complication osteoporotic fracture load a heavy burden on the whole society. The adipose tissue is the biggest endocrinology organ that has a different function on the bone. The adipocytes are differentiated from the same cell lineage with osteoblast, and they can secrete multiple adipokines with various functions on bone remolding. Recently, several novel adipokines have been identified and investigated thoroughly. In this paper, we would like to highlight the complicated relation between the bone metabolism and the novel adipokines, and it may provide us with a new target for prediction and treatment of osteoporosis.